Health Education on the Halodoc Application to Improve Mental Health in Students - Zuhrufa Amania Sholehah; Arif Widodo (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mental health is an important component of individual well-being that affects the ability to learn, work, and adapt to life's demands. Students, as a group of young adults, are vulnerable to mental health problems due to academic pressure, social issues, and demographic factors. Digital interventions, such as the Halodoc application, can be a strategic alternative to improve access to information, education, and mental health services. This study aims to analyze the effect of health education through the Halodoc application on improving students' knowledge and mental health. The study used a quasi-experimental design with 51 students from the Nursing Study Program at Muhammadiyah University Surakarta as respondents. The instruments used were the Halodoc application knowledge questionnaire and PHQ-9, both of which have been proven to be valid and reliable. Analysis using the Wilcoxon Signed Ranks Test showed a significant increase in knowledge scores from 16.9 to 34.49, as well as a decrease in depression scores from 9.39 to 2.73 (p<0.05). The results of this study prove that health education through the Halodoc application is effective in increasing students' understanding while reducing symptoms of depression. In addition, digital intervention encourages students to be more proactive in seeking information, managing stress, and building sustainable healthy behaviors.